Strengthening corporate governance in Credit Companies - Tabra Ochoa, Edison (2022)
This article argues from a legal perspective the benefits of the implementation of good corporate governance practices in microfinance institutions, especially in Credit Companies, considering it as a means to fulfill their strategic objectives, a catalyst for strengthening their financial and social performance, seeking the protection of the interests of the stakeholders, through a robust evaluation and management of risks and contributing directly to the financial inclusion of excluded groups that do not have access to the financial services offered by traditional banks and savings and loan cooperatives credit.